1998
DOI: 10.1093/ije/27.4.691
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic geographical links to human immunodeficiency virus seroprevalence among childbearing women in Montreal, 1989-1993

Abstract: Higher HIV infection rates were found among childbearing women from lower socioeconomic areas of Montreal. Increased understanding of the relationship between socioeconomic status and HIV acquisition and transmission is required to inform the development of targeted HIV prevention programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Findings consistently demonstrate that homeless individuals, including those in living homeless shelters, have higher rates of HIV infection compared to general populations (Smereck & Hockman, 1998; Corneil et al, 2006; Culhane, Gollub, & Kuhn, 2001; Robertson et al, 2004), and that HIV and AIDS incidence is inversely associated with economic wellbeing, even across gender and racial/ethnic groups (Zierler et al, 2000; Hankins et al, 1998). When considering homelessness, unstable housing, and residential transience - defined here as moving two or more times in the past 6 months (German, Davey, & Latkin, 2007; Davey-Rothwell, German, & Latkin, 2008) – significant associations have been found between housing and HIV risk behaviors.…”
Section: Introductionmentioning
confidence: 92%
“…Findings consistently demonstrate that homeless individuals, including those in living homeless shelters, have higher rates of HIV infection compared to general populations (Smereck & Hockman, 1998; Corneil et al, 2006; Culhane, Gollub, & Kuhn, 2001; Robertson et al, 2004), and that HIV and AIDS incidence is inversely associated with economic wellbeing, even across gender and racial/ethnic groups (Zierler et al, 2000; Hankins et al, 1998). When considering homelessness, unstable housing, and residential transience - defined here as moving two or more times in the past 6 months (German, Davey, & Latkin, 2007; Davey-Rothwell, German, & Latkin, 2008) – significant associations have been found between housing and HIV risk behaviors.…”
Section: Introductionmentioning
confidence: 92%
“…2001; Tyas et al . 2001) including geographic issues related to HIV/AIDS in women (Hankins et al . 1998; Wood et al .…”
Section: Geographical Contributions To Women's Health Research In Canadamentioning
confidence: 99%
“…2001; Williams 2002). Many recent studies on women and health in geographic circles have taken up the call for population health analyses with a focus on women's health status and its relationship to socioeconomic status (SES) and equality/inequality (Hankins et al . 1998; Denton and Walters 1999; Veenstra 2000; Rosenberg and Wilson 2000; Rhodes et al .…”
Section: Geographical Contributions To Women's Health Research In Canadamentioning
confidence: 99%
“…Immigrants must meet certain health and other criteria to be accepted into Canada and have enough economic resources to immigrate, likely resulting in a "healthy immigrant" effect. During our preparatory work, studies that addressed the health of migrants in Canada were identified [[10,14-19] Montpetit,[20-25]]. Of these, those that examined refugee health focused on general health [22-24] and mental health [15-18].…”
Section: Introductionmentioning
confidence: 99%
“…No study was identified which specifically addressed reproductive refugee health in Canada. Those studies focusing on reproductive health reported on migrants as a whole; results related to women refugees to Canada were not reported separately [14,19-21,25]. …”
Section: Introductionmentioning
confidence: 99%